2020
DOI: 10.1002/marc.202000175
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antimicrobial Coating on Silicone Contact Lens Using Glycidyl Methacrylate and Polyethyleneimine Based Polymers

Abstract: Contact lenses are medical devices commonly used to correct refractive errors and to maintain ocular health. Microorganisms such as bacteria that grow on the lens surface cause irritation to the eyes and can even cause loss of vision. In this paper, two different coating strategies are employed to form an efficient antimicrobial coating on contact lenses. In the first method, a presynthesized copolymer of polyethyleneimine‐graft‐polyethylene glycol methacrylate (PEI‐PEGMA) is used and the coated lenses show an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…High biocompatibility of our fabricated surface was observed by more than 90% HDF cells under 24 h exposure of extracted coating materials ( Figure 6 A). These findings were consistent with the results of a previous study by Pillai et al [ 59 ] who performed the same extraction method and showed that cell viability remained at greater than 80%; thus, these findings suggested that the coating materials did not diffuse out into the growth medium and exhibited excellent biocompatibility without toxicity in HDFs. In addition, our findings were similar to those of Dulski et al who focused on the development of silver-silica coating as a functional biomaterial surface [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High biocompatibility of our fabricated surface was observed by more than 90% HDF cells under 24 h exposure of extracted coating materials ( Figure 6 A). These findings were consistent with the results of a previous study by Pillai et al [ 59 ] who performed the same extraction method and showed that cell viability remained at greater than 80%; thus, these findings suggested that the coating materials did not diffuse out into the growth medium and exhibited excellent biocompatibility without toxicity in HDFs. In addition, our findings were similar to those of Dulski et al who focused on the development of silver-silica coating as a functional biomaterial surface [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Cytotoxicity tests were performed using MTT assays (Invitrogen Corporation, Carlsbad, CA, USA) in 96-well plates, as described previously [ 59 ]. Conditioned medium was prepared by incubating cells in growth medium for 24 h. The growth medium in 96-well plates was aspirated, and cells were washed with 1X PBS and incubated with conditioned medium for an additional 24 h. MTT assays were then performed by mixing 10 µL of 5 mg/mL MTT in 100 µL growth medium in each well, followed by a 2 h incubation.…”
Section: Methodsmentioning
confidence: 99%
“…[2,[5][6][7] One approach to fabricate silicones resistant to biofilm is to make their surfaces antimicrobial. While several methods to render silicone surfaces antimicrobial exist, including through coatings, [8][9][10][11][12][13][14][15] additives, [16][17][18][19] or surface functionalization, [20][21][22][23][24] each has advantages and disadvantages. Coatings and surface functionalization place antimicrobials directly at environmental interfaces but require multistep processing during device manufacturing.…”
mentioning
confidence: 99%
“…As expected, PDEGA brushes showed decreasing biofilm attachment as the brush thickness increased (Figure S10D). For the methacrylates, 8 out of the 10 monomers were not able to reduce bacterial cell attachments under 50%, including the zwitterionic PDMAPS and PMPC brushes, which have been well regarded for their antifouling performances , (Figure C). The less than ideal performance of these brushes may be attributed to the low grafting density of our system (0.2 chain/nm 2 ). , Following the trend observed for the acrylates, POEGMA- and PTFEMA-brushed surfaces afforded the lowest biofilm attachments of 37 and 31%, respectively.…”
Section: Resultsmentioning
confidence: 99%